2003
DOI: 10.1111/1467-9868.00392
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Statistical Evidence by using Imperfect Models: Robust Adjusted Likelihood Functions

Abstract: The strength of statistical evidence is measured by the likelihood ratio. Two key performance properties of this measure are the probability of observing strong misleading evidence and the probability of observing weak evidence. For the likelihood function associated with a parametric statistical model, these probabilities have a simple large sample structure when the model is correct. Here we examine how that structure changes when the model fails. This leads to criteria for determining whether a given likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 10 publications
1
134
0
Order By: Relevance
“…Royall and Tsou [5] referred to the preserved consistency property as the first condition of robustness. They showed that likelihood functions on the basis of such working models could be adjusted to become robust if the condition is fulfilled.…”
Section: Robust Regressionmentioning
confidence: 99%
“…Royall and Tsou [5] referred to the preserved consistency property as the first condition of robustness. They showed that likelihood functions on the basis of such working models could be adjusted to become robust if the condition is fulfilled.…”
Section: Robust Regressionmentioning
confidence: 99%
“…In order to make inference about θ in the presence of φ, we can consider the profile likelihood function L(θ,φ(θ)), whereφ(θ) is the ML estimate of φ given θ (Kalbfleisch and Sprott 1970). Royall (1997) has elaborated that the profile likelihood is a proper representation of the evidence about θ . Now, let θ be the population mean and use the inverse Gaussian with the density function…”
Section: Representing Evidence About the Parameter: The Profile Likelmentioning
confidence: 99%
“…If one applies the adjustment introduced by Royall and Tsou (2003) to L P (θ ), the resulting rescaled adjusted likelihood, denoted by L AP (θ ), is…”
Section: Poisson Surrogate Likelihood Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robust likelihood functions can be made insensitive to model misspecification (Royall and Tsou, 2003) in a regression setting (Blume et al, 2007). This is accomplished by adjusting the likelihood function, so that the adjusted likelihood behaves as if the model were correctly specified.…”
Section: Wrong Likelihood; Right Answer?mentioning
confidence: 99%